2004
DOI: 10.1200/jco.2004.07.170
|View full text |Cite
|
Sign up to set email alerts
|

Fludarabine Plus Mitoxantrone With and Without Rituximab Versus CHOP With and Without Rituximab As Front-Line Treatment for Patients With Follicular Lymphoma

Abstract: These results indicate that FM is superior to CHOP for front-line treatment of FL and that rituximab is an effective sequential treatment option. However, they also confirm that this superiority is unlikely to translate into either better PFS or OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(90 citation statements)
references
References 37 publications
4
86
0
Order By: Relevance
“…The combination of rituximab with chemotherapy containing purine analogs, such as fludarabine, further increased the CR rate to 80% [22]. The superiority in achieving CR with combinations containing purine analogs is supported by a trial published in abstract form comparing fludarabine/mitoxantrone with rituximab consolidation to CHOP/rituximab showing CR rates of 87% and 76%, respectively [23]. Recently, there has been increasing interest in using rituximab as a first-line therapy.…”
Section: Rituximab (Rituxan ® )mentioning
confidence: 99%
“…The combination of rituximab with chemotherapy containing purine analogs, such as fludarabine, further increased the CR rate to 80% [22]. The superiority in achieving CR with combinations containing purine analogs is supported by a trial published in abstract form comparing fludarabine/mitoxantrone with rituximab consolidation to CHOP/rituximab showing CR rates of 87% and 76%, respectively [23]. Recently, there has been increasing interest in using rituximab as a first-line therapy.…”
Section: Rituximab (Rituxan ® )mentioning
confidence: 99%
“…Rituximab has been shown to improve the outcome of patients with previously untreated follicular lymphoma when associated with chemotherapy (Marcus et al, 2005). Several other reports suggest that first line combination of rituximab and anthracyclinecontaining chemotherapy is able to induce very high response rates and prolonged remission, including molecular remission (Hiddemann et al, 2003;Salles et al, 2004;Zinzani et al, 2004;Czuczman et al, 2005). Both chemo-immunotherapy and RIT appear as attractive options for treatment of indolent lymphoma, but the best long-term strategy still needs to be determined.…”
Section: Toxicitymentioning
confidence: 99%
“…[52][53][54][55][56] Hematologic toxicity is the primary side effect associated with such treatment, whereas nonhematologic toxicity is rare. In a study conducted by Cohen et al, 56 patients were treated with the FCR chemotherapy regimen (4 -6 cycles of fludarabine 25 mg/m 2 per day for 3 days, cyclophosphamide 250 mg/m 2 per day for 3 days, and rituximab 375 mg/m 2 weekly); hematologic toxicity was noted in 30% of all patients, with 6% of patients developing Grade 3 or 4 neutropenia.…”
Section: Toxicitymentioning
confidence: 99%
“…These results confirmed the findings of previous studies in which similarly high response rates were reported (Table 4). 31,53 Likewise, in various small, nonrandomized trials, high overall response rates have been yielded by the combination of fludarabine and cyclophosphamide (FC). In a study conducted by Flinn et al, 45 FC (fludarabine 20 mg/m 2 per day for 5 days and cyclophosphamide 600 mg/m 2 per day for 1 day) resulted in an overall response rate of 90%.…”
Section: Fludarabine-containing Regimensmentioning
confidence: 99%
See 1 more Smart Citation